Government Policy In Distribution Of Cash Social Assistence (BST) In The New Normal Era - Nanda Herijal Putra (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study examined government policies in the distribution of Cash Social Assistence (BST) in the new normal era of the covid-19 pandemic. Research location in Darul Aman District of East Aceh Regency. This research uses a qualitative approach, data collection is done through observation, interviews and documentation. The results of the study found that government policies in the distribution of BST social assistance to the poor in the new normal era of the Covid-19 pandemic were in fact middle-class economic communities.  Although they are affected by Covid-19, many poor families affected by Covid-19 do not get BST social assistance. In the new normal era, the Government of Indonesia re-opened public spaces for community activities in the hope that the wheels of the people's economy returned to normal, but people's dependence on social assistance actually increased and the community continued to rely on social assistance from the government. Thus the community does not seek to develop itself in order to improve the family economy.